Privatization Applications In The Banking Sector In Turkey - Kaya, Yağmur; Kızılkaya, Arzu (Fırat University, 2023)
In this study, the banking sector, which is of great importance for all countries and has become increasingly important with the globalization and the fact that financial transactions do not recognize borders, is discussed. Banking, which is one of the economic growth and development indicators, is also important in our country and more emphasis has been placed on the privatization of public banks, which play an active role in the public sector and also affect the level of market development. Firstly, the concept of privatization and its aims are given, then the sections of privatization and finance and privatization banking sectors are given separately. After giving place to the theoretical and literature parts, privatization practices in the banking sector in Turkey are given. Within the scope of Sümerbank, Anadolubank, Denizbank and Etibank Bank, the first year before and after the privatization were discussed one by one, first the privatization rates were expressed with the help of graphics, and then each bank was considered separately and the income from privatization practices in Turkey ((Million $) , Foreign Direct Investment to Turkey (Million $), Inflation Rates (CPI) % and Growth Rates % in Turkey, GNP (Million $), Growth Rate in Developing Countries %, Growth Rate in Developed Countries %, Average Growth Rate in the World Using data such as %, evaluations were made on the basis of the last year before privatization, the year of privatization and the first year after.

Bu çalışmada, tüm ülkeler için büyük önem taşıyan ve küreselleşme ile birlikte finansal işlemlerin sınır tanımaması ile giderek önemi artan bankacılık sektörü ele alınmıştır. Ekonomik büyüme ve kalkınma göstergelerinden biri olan bankacılık ülkemizde de önem taşımakta ve kamu sektöründe aktif rol alan aynı zamanda piyasa gelişmişlik seviyesini de etkileyen kamu bankalarının özelleştirilmesi üzerinde daha çok durulmuştur. İlk olarak özelleştirme kavramına ve amaçlarına yer verilmiş, daha sonra özelleştirme ve bankacılık sektörleri bölümlerine ayrı ayrı yer verilmiştir. Teorik ve literatür kısımlarına yer verildikten sonra Türkiye’de bankacılık sektöründe yapılan özelleştirme uygulamalarına yer verilmiştir. Sümerbank, Anadolubank, Denizbank ve Etibank Bank kapsamında tek tek özelleştirme öncesi ve sonrası ilk yıl ele alınarak ilk önce grafik yardımı ile özelleştirme oranları ifade edilmiş olup daha sonra her banka ayrı ayrı ele alınarak Türkiye’de özelleştirme uygulamalarından elde edilen gelir ((Milyon $), Türkiye’ye Gelen Doğrudan Yabancı Yatırım (Milyon $), Türkiye’de Enflasyon Oranları (TÜFE) % ve Büyüme Oranları %, GSMH (Milyon $), Gelişmekte Olan Ülkelerde Büyüme Oranı %, Gelişmiş Ülkelerde Büyüme Oranı %, Dünyada Ortalama Büyüme Oranı % gibi veriler kullanılarak özelleştirme öncesi son yıl, özelleştirme yılı ve sonraki ilk yıl baz alınarak değerlendirmeler yapılmıştır.
TÜRKİYE’DE BANKACILIK SEKTÖRÜNDE YAPILAN ÖZELLEŞTİRME UYGULAMALARI